2017
DOI: 10.1002/asi.23844
|View full text |Cite
|
Sign up to set email alerts
|

Using interactive “Nutrition labels” for financial products to assist decision making under uncertainty

Abstract: Product information labels can help users understand complex information, leading them to make better decisions. One area where consumers are particularly prone to make costly decision-making errors is long-term saving, which requires understanding of complex concepts such as uncertainty and trade-offs. Although most people are poorly equipped to deal with such concepts, interactive design can potentially help users make better decisions. We developed an interactive information label to assist consumers with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The nutritional label combines textual explanations and graphic information, representing a best practice of dual learning theory appropriate for learners (National Research Council, 2000 ). Research supports the effectiveness of this format, demonstrating that nutritional labels, particularly those that have interactive functionality, can increase one’s understanding of a complex topic and lead to better decision making (Byrd-Bredbenner et al, 2009 ; Gunaratne & Nov, 2017 ; Kelley et al, 2010 ; Stoyanovich & Howe, 2019 ). The nutritional label as a paradigm creates a familiar entry point at which one can engage and start to question the interpretability of a model.…”
Section: Objects-to-interpret-with: Tools For Understanding Data Commentioning
confidence: 99%
“…The nutritional label combines textual explanations and graphic information, representing a best practice of dual learning theory appropriate for learners (National Research Council, 2000 ). Research supports the effectiveness of this format, demonstrating that nutritional labels, particularly those that have interactive functionality, can increase one’s understanding of a complex topic and lead to better decision making (Byrd-Bredbenner et al, 2009 ; Gunaratne & Nov, 2017 ; Kelley et al, 2010 ; Stoyanovich & Howe, 2019 ). The nutritional label as a paradigm creates a familiar entry point at which one can engage and start to question the interpretability of a model.…”
Section: Objects-to-interpret-with: Tools For Understanding Data Commentioning
confidence: 99%
“…The inclusion of more advanced navigation and searchability tools could also improve users' ability to find material of interest to them. Studies of the utility of information delivery have shown that it increases when users are able to choose and adjust relevant input parameters and display different results (Gunaratne and Nov, 2017). Allowing user interaction with complex material has also been shown to increase understanding and lead to better decision-making, especially among novice non-repeat users (Gunaratne and Nov, 2017).…”
Section: Digital Integrationmentioning
confidence: 99%
“…Their ability to influence consumers' behaviour and purchase intentions has been supported by scientific studies and is being widely exploited by online retailers (Breugelmans et al 2012;Häubl and Murray 2003;Punj and Moore 2007;Xiao and Benbasat 2007). Only recently has the inclusion of nutritional criteria into the matching algorithms between preferences and recommended products received more attention (Gunaratne and Nov 2017;Ngoc et al 2018). However, literature covering empirical user testing remains very scarce and focusses only on nutritional indicators while also from an environmental viewpoint there is a strong need for such facilitating strategies (Trattner and Elsweiler 2017).…”
Section: Conceptual Approachmentioning
confidence: 99%